Procédés de la production de l’eau chaude par l’énergie solaire pour différentes applications - NAJEM Bochra; AOUISSI Nour el Houda; AOUISSI Mokhtar (Université Amar Thelidji- Laghouat FACULTE de TECHNOLOGIE DEPARTEMENT de GENIE MECANIQUE, 2025)
This thesis focuses on the production of hot water using solar energy for various domestic and industrial applications. It highlights the importance of renewable solar energy as a clean alternative to fossil fuels. The study analyzes solar radiation data in Algeria, revealing its exceptional potential, especially in desert regions. Analytical models and simulations were used to evaluate the performance of flat plate and parabolic solar collectors. The findings demonstrate high thermal efficiency and strong economic viability. The study concludes that solar energy is a sustainable and environmentally friendly solution for hot water production and energy needs.